Qualitative and Numerical Analysis of an SVEIR Model for HIV-HBV Co-Infection - Maria Lobo; Adelya Hanaya Mage; Ariyanto Ariyanto (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2026)
The dynamics of HIV-HBV co-infection present significant epidemiological challenges, particularly in resource-limited areas. This study employs the SVEIR mathematical model to explore the transmission and control of HIV-HBV co-infection in Kupang City, Indonesia. Using the Next Generation Matrix method, the basic reproduction number (R0) was estimated at 1.36, indicating persistent disease transmission without effective intervention. Sensitivity analyses identified HBV vaccination coverage and treatment accessibility as critical parameters significantly influencing infection dynamics. Numerical simulations validated the theoretical model, demonstrating that increased vaccination rates and enhanced antiviral therapy access substantially reduce co-infection prevalence. Furthermore, equilibrium analyses revealed that effective interventions capable of lowering R0 below unity could transition the system from persistent endemicity toward disease elimination. These results emphasize the necessity of integrated intervention strategies, including expanded HBV vaccination, improved antiviral therapy access, and comprehensive community education to mitigate HIV-HBV co-infection. Future research should address existing limitations, incorporating behavioral and socioeconomic determinants to enhance model accuracy and applicability.